Penguatan Literasi Al-Quran pada Mahasantri (studi kasus di pesantrean kampus Bin Baz) - Qiyadah Robbaniyah; Mega Primaningtyas; Ahmad Fadlur Rahman Bayuny (At Turots: Jurnal Pendidikan Islam, 2024)
The purpose of this study was to determine the strengthening of Al-Quran literacy in female students (a case study at the Bin Baz Campus Islamic Boarding School). This research method is a qualitative method with a case study approach, collecting data by interviews, observation and documentation. The application of Al-Quran Literacy at the Bin Baz Campus boarding school (Case Study at the Bin Baz Campus boarding school) in the month of Ramadan has a special theme, namely IRAMA (The Beauty of Ramadan Reaching Taqwa) which is realized in activities that supports Al-Quran literacy both from female students and the local community. IRAMA activities in the month of Ramadan, namely; 1) Shohabiyyatul Qurani, namely the TPA Program, where female students conduct activities to teach the Koran to children, 2) Islamic Speak, which is a cult program that will be carried out every morning prayer, 3) Tahfidz, 4) Echoes of Khatmil Quran: namely recitations 30 juz performed Ba'da tarawih prayer with a duration of 1 hour. 5) Taraweeh prayer. 6) Ramadan study; Strengthening Al-Quran literacy for students at the Bin Baz campus Islamic boarding school in the month of Ramadan namely; 1) In-depth Understanding of Religion, 2) Strengthening Islamic Identity, 3) Developing Self-Quality, 4) Calming the Soul and Mental, 5) Increasing the Quality of Worship, 6) Development of Islamic Community.